Radiolabeling of platelets with 99mTc-HYNIC-Duramycin for in vivo imaging studies - Merkel, Keresztély (2024)
Following the in vivo biodistribution of platelets can contribute to a better understanding of their physiological and pathological roles, and nuclear imaging methods, such as single photon emission tomography (SPECT), provide an excellent method for that. SPECT imaging needs stable labeling of the platelets with a radioisotope. In this study, we report a new method to label platelets with 99mTc, the most frequently used isotope for SPECT in clinical applications. The proposed radiolabeling procedure uses a membrane-binding peptide, duramycin. Our results show that duramycin does not cause significant platelet activation, and radiolabeling can be carried out with a procedure utilizing a simple labeling step followed by a size-exclusion chromatography-based purification step. The in vivo application of the radiolabeled human platelets in mice yielded quantitative biodistribution images of the spleen and liver and no accumulation in the lungs. The performed small-animal SPECT/CT in vivo imaging investigations revealed good in vivo stability of the labeling, which paves the way for further applications of 99mTc-labeled-Duramycin in platelet imaging.